The Effect of Jigsaw Cooperative Learning Model on Learning Outcomes of Dribbling and Passing Using the Back of the Foot Football Game in Class VII Students of SMP - Ni Putu Anggreni; I Wayan Repiyasa; Komang Ayu Krisna Dewi (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2022)
This study aims to determine the effect of the jigsaw cooperative learning model on learning outcomes of dribbling and passing by using the instep of a soccer game in class VII students of SMP Negeri 1 Pekutatan. This type of research is quasi-experimental research. The population is all students in class VII A and VII B of SMP Negeri 1 Pekutatan for the 2021/2022 school year with a total of 66 students. The sample used random sampling. The research was conducted in twelve meetings. Learning outcome data is collected by means of objective tests. Data collection methods in the form of attitudes, knowledge and skills were then analyzed using the SPSS 16.0 For Windows program. The average dribbling learning result of the experimental group was 38.0373 while in the control group the average was -10.0876. The average passing learning result from the experimental group was 39.3394 while in the control group the average was -15.5548. The results of this study indicate that the jigsaw type cooperative learning model affects the learning outcomes of dribbling and passing